An Overview of Fanconi Anemia: A Genetic Disorder - Hemin Johnson (International Journal of Oncological Nursing and Practices, 2024)
Fanconi Anemia (FA) is a rare genetic disorder caused by DNA repair defects due to pathogenic variants in one of 21 genes. It is the primary cause of inherited bone marrow failure, marked by pancytopenia. Clinically, Fanconi Anemia (FA) is associated with congenital malformations in multiple systems, resulting in progressive bone marrow failure and heightened cancer risk, especially in the urogenital region and the head and neck. There are approximately 20 FA-related genes, but not all are impacted by mutations. These genes play a critical role in protecting against DNA damage accumulated over a lifetime. Fanconi anemia affects about 1 in 136,000 newborns, with an incidence of 1 in 100,000 to 250,000 births Mutations in three particular genes—FANCA, FANCC, and FANCG—are responsible for 80% to 90% of cases of Fanconi Anemia (FA). Clinical symptoms typically manifest in early childhood or young adulthood, with signs at birth including growth deficiencies, skeletal anomalies, small head or eyes, and abnormal skin pigmentation. In young children, symptoms can include unexplained fatigue, frequent infections, recurrent nosebleeds, easy bruising, blood in stool or urine, and other haematological issues. Several disorders linked to Fanconi Anaemia (FA) include Diamond Blackfan Anemia (DBA), Paroxysmal Nocturnal Hemoglobinuria (PNH), Schwachman-Diamond Syndrome (SDS), and Bloom Syndrome (BS). Diagnostic assessments involve array comparative genomic hybridization (array-CGH), cytogenetic testing, and molecular testing. Treatment options include oral androgen administration, recommendations for hematopoietic stem cell transplantation (HSCT), vitamin D supplementation, various therapies, hearing aids, blood transfusions, and genetic counselling.
Keywords: Array comparative genomic hybridization (array-CGH); FANCA; FANCC; FANCG; Fanconi anaemia (FA); and bloom syndrome (BS); schwachman – diamond syndrome (SDS)